Impacto das queimas de biomassa na qualidade do ar de cidades da Bolívia - Veneros, Eva Maria Mollinedo (2021)
Biomass burning (BB) is very frequent in South America during the dry season (July - October) and the emitted pollutants can be transported regionally, affecting human health, biodiversity and climate. Previous research showed that the pollutants emitted by BB in the Amazon region reached rural regions in the state of La Paz (Bolivia). This study focused on the impact of BB on the air quality in Bolivia's large cities (La Paz, Cochabamba and Santa Cruz). Concentrations of particulate matter with a aerodynamic diameter smaller than 10 µm (PM10), nitrogen oxides (NOx) and ozone (O3) measured in situ by the Air Quality Monitoring Network (MoniCA) were analyzed in the period 2017-2019. This information was supplemented with satellite products of carbon monoxide (CO) content from TROPOMI sensor (Sentinel 5P satellite) and aerosol optical depth (AOD) from MODIS (Terra and Aqua satellites), and concentrations of O3 and fine particulate matter (PM2.5) from EAC4 reanalysis. The BB impact on the urban air quality was quantified by comparing the satellite and reanalysis mean values during the burning and no-burning periods. The long-range transport of pollutants was identified by analyzing the air mass back-trajectories and the Potential Source Contribution Function (PSCF) for Cochabamba in September 2019. The results showed that the Bolivian lowlands were highly impacted by fire smoke transported by the low-level jet from the Amazon and Cerrado regions (in Brazil and Bolivia) to the study area. Santa Cruz was the most affected city, due to its proximity to the fire foci, with values of PM2.5, O3, CO and AOD between 1.4–2.4 times higher compared to the period without fires. No AOD changes were observed in La Paz and Cochabamba during the burning season, but PM2.5, O3 and CO concentrations were 1.1–1.6 times higher. The regional transport of pollutants was observed in Cochabamba in September 2019 mainly: i) in the episodes of high nocturnal PM10 (80–180 µg/m3) and O3 (20–45 µg/m3) concentrations measured in situ, and ii) in the air mass backtrajectories over regions with a large number of fire foci, with 77% coming from the north and northwest of the country, and 23% from the north of Argentina and Paraguay in the last week of the month. The PSCF function indicated a 35–50% probability that the fires in Paraguay and Argentina caused the high nocturnal O3 concentrations observed in Cochabamba for a specific event. Thus, the urban air quality in Bolivia can be deteriorated by BB smoke at the regional scale and with cross-border contributions. International cooperation among the countries in South America is needed to control and reduce fire practices, to protect human health and ecosystems and reduce the impact on global warming.